THE DYNAMICS OF LOCAL GOODS TRADE AND IMPORTS IN THE SERIKIN CROSS-BORDER MARKET: AN ANALYSIS OF INDONESIA-MALAYSIA ECONOMIC INTERACTIONS THROUGH LITERATURE REVIEW - Gunawan Widjaja; Wagiman (Review of International Economy and Finance, 2026)
This study analyses the dynamics of local and imported goods trade in the Serikin Cross-Border Market as a reflection of economic interaction between Indonesia and Malaysia using a literature review method. This study explains how local and imported goods play a role in cross-border economic activities, while strengthening socio-cultural relations in the border region. Through a synthesis of various academic literature, it was found that local goods trade not only supports the economy of border communities but also preserves cultural identity and strengthens social networks. Meanwhile, the flow of imported goods indicates a high level of economic interdependence between the two countries, but also poses challenges such as intensifying business competition and the risk of illegal goods entering the market. The results of this study emphasise the importance of balanced and adaptive cross-border market management so that trade can take place in a healthy and sustainable manner, thereby contributing positively to regional economic development and bilateral relations between Indonesia and Malaysia.